Sufisme di Priangan:Doktrin, Ritual, dan Sosial-Politik - Abdurahman, Dudung (Research and Development Institution, Darussalam Institute for Islamic Studies, 2016)
Tarekat community in Priangan performed religious and social-political movements that keep changing along with Moslems’ dynamic movement and political development of Indonesia . The change and diversity of the tarekat movement occurs in its three communities, namely: Godebag community in Tarekat Qadiriyah wa Naqsyabandiyah (TQN) Suryalaya, Wara’i community in Tarekat Idrisiyah Pagendingan, and Tijani community in Tarekat Tijaniyah Garut. This research reveals several significant issues. First, the core of Sufi’s doctrine that is developed in tarekat ritual system functions to strengthen spirituality and morality of the tarekat community. Different Sufi’s doctrines in each tarekat result in different social-political relationship among those three tarekat communities. Second, the social-political roles, relationships and participations of the tarekat community change along with the political changes of the government that ruled both in colonial era and in the Indonesian independence. Third, the social-political movement of the tarekat community can be differentiated into: inclusive-pragmatism of Godebag community, exclusivism-fundamentalism of Wara’i community, and fundamentalism-pragmatism of Tijani com-munity. Fourth, tarekat community movements promote spiritual and moral public education in social-political life in Indonesia . Based on the findings, it can be concluded that social-political movements of tarekat community are in line with Sufi’s doctrines that change into various movement types. Therefore, tarekat community is predicted to develop changing social-political movements.